Integrating stability and flexibility in complex socio-technical systems: the case of the GB rail system - Calero Gonzalez, Maria C. (2025)
Conventional approaches to operational safety management rely on centralised hierarchical control structures, emphasising strict adherence to standards to minimise risks and uncertainty. This method aims to maintain stability and reduce variability in processes and behaviours, creating a predictable operational environment. This centralised control approach is dominant in modern complex sociotechnical systems in which safety is critical. Researchers have challenged this approach, arguing that the complexity and uncertainty in modern systems render preestablished, standardised control measures insufficient. They advocate for developing adaptive systems capable of navigating complexity and uncertainty, arguing that flexibility to handle contingencies in context by local actors is crucial.